PERBEDAAN HASIL BELAJAR SISWA ANTARA PENGGUNAAN METODE MIND MAPPING DENGAN METODE DISKUSI TEMA INDAHNYA KEBERSAMAAN PADA SISWA KELAS IV DI SDN 1 BESUKI TAHUN PELAJARAN 2015/2016 - Juhariyah Juhariyah; Indah Lestari Setiorini (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2015)
This study aims to determine Differences Between Student Results Using Mind Mapping Method Method Discussion Beautiful Theme Mutual Students of Class IV in SDN 1 Besuki the Academic Year 2015/2016 . The method used in this research is quantitative experimental methods , data collection method used was a test , and documentation . The instrument used to measure student learning outcomes is a multiple choice test . In the test the hypothesis , researchers used a t-test . The results showed that the students' learning outcomes by using Mind Mapping method is better in comparison with the method of discussion . It can be seen from the value of the average scores of students in the experimental class 75.625 while the average scores obtained in the control class students is 51.45 . The difference between the average value of the experimental class and control class is equal to 24.175 , which means Mind Mapping method is better in comparison with the method of discussion . So that in view of the average value that there are differences in learning outcomes of students who obtained when applied Mind Mapping method and the method of discussion in the experimental class and control class